The circle blueprint : decoding the conscious and unconscious factors that determine your success - Skeen, Jack, 1950- (Online access with DDA: Askews (Psychology), 2017)
A roadmap to fulfillment, with practical tools for the journey The Circle Blueprint is your personal guide to fulfillment. Are you thriving or just surviving' Are you energized, balanced, and happy' This book helps you dig to the root of the problem, and gives you a roadmap for getting your life on a more positive trajectory. You'll begin with an honest assessment of your current situation, and the life choices that got you there; this is your Circle, and through it, almost anything becomes possible. Your Circle can be adjusted-expanded, narrowed, balanced, or thrown off-kilter-to steer your life where you want it to go. Your Circle must be tended to, and whether you realize it or not, you make these choices every single day. This book helps you define your Circle, master it, and create the life you want to live. Finding satisfaction doesn't mean starting a whole new life, it means reshaping the one you have to keep what's working and adjust what's holding you back. This book gives you the tools and insight you need to make the journey, with practical exercises to guide you through each step of the way.-Think about how your life choices affect your emotional well-being -Map your existing Circle to your current levels of life satisfaction -Expand and balance your Circle to align more closely to your vision -Discover the fulfillment of living life with purpose Wanting more doesn't mean not liking what you have, it's simply an acknowledgment that there is room for improvement. Change is not only possible; it's often inevitable-but it's up to you to dictate the course of these changes. The Circle Blueprint helps you chart your path, and gives you the tools you need to reach that destination.